2017
DOI: 10.1111/jeu.12408
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Detection of BrdU/EdU Incorporation Assays Alter the Calculation for G1, S, and G2 Phases of the Cell Cycle in Trypanosomatids

Abstract: Trypanosomatids are the etiologic agents of various infectious diseases in humans. They diverged early during eukaryotic evolution and have attracted attention as peculiar models for evolutionary and comparative studies. Here, we show a meticulous study comparing the incorporation and detection of the thymidine analogs BrdU and EdU in Leishmania amazonensis, Trypanosoma brucei, and Trypanosoma cruzi to monitor their DNA replication. We used BrdU- and EdU-incorporated parasites with the respective standard dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 45 publications
5
33
0
2
Order By: Relevance
“…Thus, G1 phase duration was estimated to be 3.37 h or 0.397 ccu ( Figure 1D). 15 These new precise values for the duration of G1 and S phase in T. brucei TREU927 share close similarities to those obtained for T. brucei Lister strain 427, which were also estimated by EdU incorporation (15) or by counter-flow elutriation (27). This similarity suggests that different strains of the same species (T. brucei) probably do not have significant differences in cell cycle lengths.…”
Section: Edu Allows a More Accurate Estimation Of S Phase Duration Insupporting
confidence: 67%
See 3 more Smart Citations
“…Thus, G1 phase duration was estimated to be 3.37 h or 0.397 ccu ( Figure 1D). 15 These new precise values for the duration of G1 and S phase in T. brucei TREU927 share close similarities to those obtained for T. brucei Lister strain 427, which were also estimated by EdU incorporation (15) or by counter-flow elutriation (27). This similarity suggests that different strains of the same species (T. brucei) probably do not have significant differences in cell cycle lengths.…”
Section: Edu Allows a More Accurate Estimation Of S Phase Duration Insupporting
confidence: 67%
“…The duration of S phase starts when the first cytokinesis-labeled cell appears, extends throughout the period of detection for all cytokinesislabeled cells and ends when some unlabeled cells appear again. Of note, this assay was carried out according to a protocol described in a previous study (15).…”
Section: S Phase Length Analysis Using the Measurement Of Cytokinesismentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, an image-based assay to assess parasite replication utilising EdU as a chemical probe was developed to determine compound activity against Leishmania donovani [20]. The incorporation of EdU and BrdU has been compared in T. cruzi epimastigotes and it was found that EdU was most effective for monitoring DNA replication because of its sensitivity and that DNA denaturation is not required [21].…”
mentioning
confidence: 99%